Causal Factors Influencing Decision-Making Use Environmentally Friendly Building Materials of Construction Business Operators in Bangkok - Lawsakul, Arthit; Kuensman, Wanphen; Photiwichayanon, Kanchana (Asia Social Issues, 2025)
This study explores the decision-making processes among construction business operators in Bangkok regarding the use of environmentally friendly building materials, within the context of heightened global emphasis on environmental sustainability. In response to increasing consumer awareness of environmental impacts, particularly in the residential housing sector, this research aimed to identify the causal factors influencing these decisions. Employing quantitative methods, the study analyzed responses from 320 legally registered construction contractors who had used eco-friendly materials in at least five housing projects during 2023. Data were gathered via questionnaires and analyzed using a structural equation model. The findings indicate that the primary determinants of material choice were the operators’ skills and product trust, with the former showing the most decisive influence. The 4Ps marketing mix and service quality followed these factors in significance. The insights provided by this research are crucial for manufacturers, contractors, and regulatory bodies aiming to promote the adoption of sustainable materials in Thailand’s construction industry, thereby enhancing environmental conservation and reducing pollution from building activities.